Steamboats COLUMBIAN (left), CANADIAN (center), and VICTORIAN (right), in port at Dawson, Yukon Territory, 1899. - Hegg & Co.
Caption on image: "Canadian Development Co.'s three steamers in port" PH Coll 246.106 [Meed journal: "Canadian Development Co.'s three steamers in port of Dawson , 1899. "Columbian,", "Canadian," and "Victorian""] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number